Analiza struktur organizacji i działalności niektórych stowarzyszeń agroturystycznych w Polsce - Elżbieta Wielgosz; Adam Szember (Agronomy Science, 2006)
The objective of the investigation was to observe the effect of selected plants on the number and activity of soil microorganisms. Soil samples for analyses were collected from the rhizosphere, and control samples were taken from fallow soil. The total number of bacteria and the total number of fungi as well as the number of ammonification bacteria and the number of lipolytic bacteria were determined by using dilution plate technique. The number of cellulolytic bacteria and the number of nitrifying bacteria were determined on the basis of the titre. The most probable number of bacteria was taken from Mc Crady tables. The respiratory activity was measured on the basis of the quantity of emitted CO2 according to Rühling et al. The highest respiratory activity was stated under Sida heramphrodita and Helianthus tuberosus. In general, more CO2 was emitted in autumn, which is the period of increased mineralization of organic matter in soil. Both vetch and chickling vetch, despite their acid reaction, were found to stimulate the development of ammonification, nitrifying, cellulolytic, and lipolytic bacteria. The highest total number of bacteria and the relatively high number of fungi were stated in the soil under these plants. The smallest number of fungi was stated in the fallow soil. Thus, the relation of bacteria to fungi was the highest there. Kaszubska vetch and chickling vetch proved to the most positive effect on the soil microbial communities studied. They may therefore be used to improve the biological activity of degraded soils.